Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar IPA Menggunakan Model PBL, SAVI, dan GI pada Siswa Kelas V SD - Hasanah, Uswatun; Rini, Tika Puspita Widya (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The low levels of critical thinking skills and student learning outcomes in the science curriculum of class V at SDN Lokrawa Barito Kuala are the study's main concerns. This is because learning in the classroom is still primarily focused on the teacher, which discourages students from speaking up for what they think is right, does not offer learning exercises that encourage critical thinking, puts students in a passive role when solving problems, and results in a lack of comprehension of the subject matter. This may be the best course of action using the paradigms of group research, problem-based learning, and SAVI (Somatic, Auditory, Visual, and Intellectual). Action research in the classroom is used in this study (PTK). This class action research study aims to demonstrate the enhancements in student learning outcomes and critical thinking abilities. Exams for individual evaluation are utilized to gauge the learning objectives of students, and observation sheets are employed to gather data on the critical thinking and action abilities of both teachers and students. The study's findings demonstrated that, at meeting 4, the pupils' and teacher's traditional activity met both the very good and the extremely active requirements. At meeting 4, 93% of the students' learning objectives and critical thinking abilities were satisfied in a conventional way. These findings imply that the application of group investigation models, problem-based learning, and SAVI (Somatic, Auditory, Visual, Intellectual) might enhance students' learning outcomes in science courses as well as teachers' and students' critical thinking abilities.